Rings of separated power series and quasi-affinoid geometry - Lipshitz Leonard; Robinson Zachary (Paris Societie Mathematique de France, 2000)
The papers in this volume present a theory of rigid analytic geometry over an ultrametric field K that generalizes the classical affinoid theory to the setting of relative rigid analytic geometry over an open polydisc. The 1st paper develops the theo
Keywords: Non-Archimedian analysis; Rigid analytic geometry